Journal of English as a Lingua Franca (De Gruyter Mouton, 2012)
Journal of English as a Lingua Franca is the first journal to be devoted to the rapidly-growing phenomenon of English as a Lingua Franca. The articles and other features explore this global phenomenon from a wide number of perspectives, including linguistic, sociolinguistic, socio-psychological, and political, in a diverse range of settings where English is the common language of choice.